Pediatric Withdrawal Identification and Management - Whelan, Katherine T.; Heckmann, Maura K.; Lincoln, Patricia A.; Hamilton, Susan M. (Journal of Pediatric Intensive Care, 2015)
Sedation administered by continuous intravenous infusion is commonly used in the pediatric intensive care unit to facilitate and maintain safe care of children during critical illness. Prolonged use of sedatives, including opioids, benzodiazepines, and potentially other adjunctive agents, is known to cause withdrawal symptoms when they are stopped abruptly or weaned quickly. In this review, the common signs and symptoms of opioid, benzodiazepine, and dexmedetomidine withdrawal will be discussed. Current tools used to measure withdrawal objectively, as well as withdrawal prevention and management strategies, will be discussed.
Keywords: pediatric withdrawal; pediatric narcotic withdrawal; pediatric benzodiazepine withdrawal; dexmedetomidine withdrawal